2019
DOI: 10.1186/s40814-019-0481-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome measurement in community-acquired pneumonia: feasibility of routine application in an elderly hospitalized population

Abstract: Background Community-acquired pneumonia (CAP) is a leading cause of morbidity and mortality worldwide, but few studies have evaluated the feasibility of routine patient-reported outcome measures (PROMs) in this illness. This study investigates the feasibility and limitations of three credible PROM instruments in a representative hospitalized cohort to identify potential barriers to routine application. Methods A sample of multimorbid hospitalized subjects meeting a stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Non‐compliance or adherence issues, 28 unreasonable patient expectations, 29 and unmet patient health needs 29 have been identified as other factors that may lead to complex doctor‐patient relationships. Even patient reported outcome measures (PROMS) for a single condition such as community acquired pneumonia are highly complex and difficult to interpret in the diversity of primary care 30 . The nature of primary care is to focus on the person, not the disease.…”
Section: Complex Adaptive Systems and Primary Carementioning
confidence: 99%
See 1 more Smart Citation
“…Non‐compliance or adherence issues, 28 unreasonable patient expectations, 29 and unmet patient health needs 29 have been identified as other factors that may lead to complex doctor‐patient relationships. Even patient reported outcome measures (PROMS) for a single condition such as community acquired pneumonia are highly complex and difficult to interpret in the diversity of primary care 30 . The nature of primary care is to focus on the person, not the disease.…”
Section: Complex Adaptive Systems and Primary Carementioning
confidence: 99%
“…Even patient reported outcome measures (PROMS) for a single condition such as community acquired pneumonia are highly complex and difficult to interpret in the diversity of primary care. 30 The nature of primary care is to focus on the person, not the disease. PROMS most often perpetuate simplistic disease-focused management.…”
Section: Complexity and Value-based Carementioning
confidence: 99%
“…The primary treatment approach for CAP focuses on antimicrobial therapy. Depending on the patientʼs condition, antibiotics such as doxycycline, minocycline, and amoxicillin are administered, or symptomatic treatments such as ibuprofen and acetaminophen are provided [8] . Traditional Chinese medicine has also shown promising therapeutic effects, and studies have demonstrated that integrated traditional and Western medicine treatments effectively improve clinical symptoms and quality of life in patients [9] .…”
Section: Introductionmentioning
confidence: 99%